Clonal haematopoiesis as a risk factor for therapy-related myeloid neoplasms in patients with chronic lymphocytic leukaemia treated with chemo-(immuno)therapy - Voso, Maria-Teresa; Pandzic, Tatjana; Falconi, Giulia; Denčić-Fekete, Marija; De Bellis, Eleonora; Scarfo, Lydia; Ljungström, Viktor; Iskas, Michail; Del Poeta, Giovanni; Ranghetti, Pamela; Laidou, Stamatia; Cristiano, Antonio; et al. (British journal of haematology, 2022)
Clonal haematopoiesis of indeterminate potential (CHIP) may predispose for the development of therapy-related myeloid neoplasms (t-MN). Using target next-generation sequencing (t-NGS) panels and digital droplet polymerase chain reactions (ddPCR), we studied the myeloid gene mutation profiles of patients with chronic lymphocytic leukaemia (CLL) who developed a t-MN after treatment with chemo-(immuno)therapy. Using NGS, we detected a total of 30 pathogenic/likely pathogenic (P/LP) variants in 10 of 13 patients with a t-MN (77%, median number of variants for patient: 2, range 0-6). The prevalence of CHIP was then backtracked in paired samples taken at CLL diagnosis in eight of these patients. Six of them carried at least one CHIP-variant at the time of t-MN (median: 2, range: 1-5), and the same variants were present in the CLL sample in five cases. CHIP variants were present in 34 of 285 patients from a population-based CLL cohort, which translates into a significantly higher prevalence of CHIP in patients with a CLL who developed a t-MN, compared to the population-based cohort (5/8, 62.5% vs. 34/285, 12%, p = 0.0001). Our data show that CHIP may be considered as a novel parameter affecting treatment algorithms in patients with CLL, and highlight the potential of using chemo-free therapies in CHIP-positive cases.
Keywords: CLL; rizikové faktory; Neoplasms, Second Primary; t-MN; Leukemia, Lymphocytic, Chronic, B-Cell; Mutation; mutace; CHIP and FCR; lidé; Risk Factors; chronická lymfatická leukemie; sekundární malignity; Antineoplastic Combined Chemotherapy Protocols; Clonal Hematopoiesis; Humans; klonální hematopoéza; protokoly protinádorové kombinované chemoterapie